(3OejI GdbUQ hYUQI Cgd GdYUQs - (3JPjjd CHhGdMSf Ydj Hf GdMSf GdHGNQRjs
(3ChdgG (B:s
(3CMeO Gddg Ydi eG CSHZ ef CPjGd CaVGdg hCTcQg Ydi eG GaQZ ef SLGd fhGdg s
(3BNQgG (B:s
(3ef BNQ JaQjW LGA ajg HYO JeGe GdcJGH(B: (3NPgG fJjLI WHY Ef CgHJ Hg CLGH aj GhbJ eKd GdYjf efaLQg hGdMeO ddg QH GdYGdejf s
(3GfXQ Qbe (B661s
(3Qbe (B1046 (3JGQjNs
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B446 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B178 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs